2017
DOI: 10.1021/acs.energyfuels.6b02780
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Moisture Content in Coal on the Pyrolysis Behavior in an Indirectly Heated Fixed-Bed Reactor with Internals

Abstract: The fixed-bed reactor with internals has been proposed to enhance the pyrolysis performance for coal. In this study, the pyrolysis behavior of different coal moisture contents and the reaction mechanism were investigated in an indirectly heated fixed-bed reactor with internals. The results showed that, at a furnace temperature of 900 °C, the increased coal moisture content went from 0.41 to 11.68 wt % and significantly modified the temperature fields, thereby prolonging the pyrolysis time to reach 500 °C and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…When a is 25, few C 5 þ compounds are formed during pyridine pyrolysis. This phenomenon is in agreement with previous experimental studies [7,8]. Results show that water molecules greatly inhibit polycondensation reactions and modify pathways to char, tar and gas, which is of great significance to control nitrogen migration during coal pyrolysis.…”
Section: Effects Of Water On Polycondensation Compoundssupporting
confidence: 92%
See 2 more Smart Citations
“…When a is 25, few C 5 þ compounds are formed during pyridine pyrolysis. This phenomenon is in agreement with previous experimental studies [7,8]. Results show that water molecules greatly inhibit polycondensation reactions and modify pathways to char, tar and gas, which is of great significance to control nitrogen migration during coal pyrolysis.…”
Section: Effects Of Water On Polycondensation Compoundssupporting
confidence: 92%
“…According to previous studies [8,9], pyridine molecules undergo ring opening reactions firstly during pyrolysis. Fig.…”
Section: Effects Of Water On Ring-opening Reactionsmentioning
confidence: 93%
See 1 more Smart Citation
“…Pyrolysis, which is defined as the rapid decomposition of organic materials in the absence of oxygen, is a promising thermal approach that can be used to convert biomass into energy and chemical materials, especially in China. Biomass pyrolysis poly-generation technology employs modern biomass carbonization technology at its core, with biochar, pyrolysis gas, and pyrolysis oil as key coproducts. , Thermochemical conversion of agricultural wastes has a unique ability to address the food, water, and energy nexus. , Biochar has multiple uses, e.g., as solid fuel, an adsorbent material, a soil amendment, and a component of slow release fertilizer, thereby helping to address many challenges in sustainable food production, environmental contamination, and climate change mitigation, as well as adaptation. Pyrolysis gas is a clean fuel that can be used for heating and cooking applications . The liquid coproducts of biomass pyrolysis can be used as fuel or source of chemicals, such as phenols and organic acids. , A recent survey of crop straw resources in China showed that the theoretical resource of major crop (corn, wheat, rice, cotton, et al) straw in 2015 was ∼1.04 billion tons (see Table ) and the collectible resource was as much as 900 million…”
Section: Introductionmentioning
confidence: 99%
“…Hu et al [22] investigated the pyrolysis behavior and reaction mechanisms of coal samples containing different moisture contents. They found that the moisture content had a significant influence on the tar yield and light tar content, and H 2 O could upgrade the low-rank coal during pyrolysis [23].…”
Section: Introductionmentioning
confidence: 99%